Ocular surface complications following biological therapy for cancer - Ma, Kevin Sheng-Kai; Tsai, Ping-Feng; Hsieh, Tina Yi-Jin; Chodosh, James (Frontiers in Toxicology, 2023)
Novel and highly effective biological agents developed to treat cancer over the past two decades have also been linked to multiple adverse outcomes, including unanticipated consequences for the cornea. This review provides an overview of adverse corneal complications of biological agents currently in use for the treatment of cancer. Epidermal growth factor receptor (EGFR) inhibitors and immune checkpoint inhibitors are the two classes of biological agents most frequently associated with corneal adverse events. Dry eye, Stevens-Johnson syndrome, and corneal transplant rejection have all been reported following the use of immune checkpoint inhibitors. The management of these adverse events requires close collaboration between ophthalmologists, dermatologists, and oncologists. This review focuses in depth on the epidemiology, pathophysiology, and management of ocular surface complications of biological therapies against cancer.